Void avoidance energy efficient pressure-based opportunistic routing for underwater wireless sensor networks - Abdullahi, Bashir (2019)
Underwater Wireless Sensor Networks (UWSNs) is considered promising technology for collection of data from underwater environment. It consists of energy limited nodes. Acoustic links is the most reliable medium of communication. Energy consumption is much high when it comes to transmission and reception of packets. The most challenging problem in UWSN is routing data packets successfully with minimum energy consumption and high packet delivery ratio. UWSNs is characterized with unique features such as dynamic topology, very high propagation delay, extreme energy consumption and high packet loss. However, Opportunistic routing (OR) is one of the promising approaches that can work efficiently in underwater. An energy efficient opportunistic routing algorithm should be used to handle efficiently the three main problem of UWSNs. The issues are selecting best forwarding node, communication void and duplicate forwarding suppression. Therefore, the research is to design and develop void avoidance and energy efficient pressure-based routing for UWSNs. To deal with improper selection of next forwarding node, Best Forwarding Node Depth Based Routing (BFNDBR) algorithm is introduced to select the best next forwarding nodes using node information based on sorting nodes and selecting the highest residual energy and highest link quality node. Then the BFNDBR is improved to tackle communication void. As the result the Void Avoidance Depth Based Routing (VADBR) algorithm is presented to detect void and trapped nodes and avoid them in packet forwarding process. Finally, The VADBR algorithm is modified and improved to deal with duplicate forwarding suppression. Therefore, Duplicate Packet Forwarding Suppressor Depth Based Routing algorithm (DPFSDBR) is introduced to improve efficiency of overhear and suppression algorithm by introducing dynamic forward selection method. To evaluate the performance of the proposed algorithms, AquaSim an NS2 based simulator was used as network simulator and 50 runs of experiments were conducted, and results were compared with existing algorithms. The results indicate that the introduced algorithms outperform others in terms of total energy consumption (27% - 42%) and packet delivery (2% - 16%) and network lifetime (20% - 40%).